Synthesis of Glucose Based Water Soluble Molecular Tweezers as Molecular Recognition Scaffolds - Lalit Sharma (E-Journal of Chemistry)
Dry heating of 4,4’-methylenedianiline and N,N’-dimethyl-4,4’-methylenedianiline with 5,6-anhydro-1,2-o-isopropylidene-α-D-glucofuranose afforded molecular tweezers having tertiary amino group linked to C-6 of the glucose moiety. These molecular tweezers on deprotection with dilute acid yielded water soluble analogs which were explored for the solubilization of neutral arenes viz. naphthalene, biphenyl, durene, fluorene, anthracene and phenanthrene in acidic aqueous medium. These solid liquid extraction studies revealed that 6,6’-(N,N’-dimethyl-4’’,4’’’-methylenedianilino) bis (α-D-glucopyranose) causes an approximate 31 fold increase in the solubility of biphenyl in aqueous medium and has best complementarity for naphthalene by forming 1:1 complex.